2012
DOI: 10.1287/mnsc.1110.1493
|View full text |Cite
|
Sign up to set email alerts
|

Contractual Flexibility, Rent Seeking, and Renegotiation Design: An Empirical Analysis of Information Technology Outsourcing Contracts

Abstract: This paper examines renegotiation design in contracts for outsourced information technology (IT) services. Whereas prior literature in information systems has highlighted the likelihood of ex post rent seeking engendered by renegotiation, we build upon literature on incomplete contracts to posit that renegotiation can be Pareto improving by incorporating contingencies revealed ex post. Research on contract renegotiation has been hampered by two sets of challenges: the lack of appropriate data and empirical cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 72 publications
2
81
0
2
Order By: Relevance
“…Positional embeddedness also conveys centrality or prestige to nodes with which no direct ties exist due to the fact that the centrality of each node is not only a function of its connected ties but also of remote ties separated by a few other nodes. Mani et al 2010, Susarla 2012. Prior literature has demonstrated that reputation mechanisms are not very effective in the IT services sector (Banerjee and Duflo 2000).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Positional embeddedness also conveys centrality or prestige to nodes with which no direct ties exist due to the fact that the centrality of each node is not only a function of its connected ties but also of remote ties separated by a few other nodes. Mani et al 2010, Susarla 2012. Prior literature has demonstrated that reputation mechanisms are not very effective in the IT services sector (Banerjee and Duflo 2000).…”
Section: Discussionmentioning
confidence: 99%
“…When vendors anticipate bargaining over ex post surplus, they are reluctant to invest in noncontractible, client-specific investments (Klein et al 1978). With complexity and uncertainty in exchange conditions, vendor firms, who commit to exchange terms over a long horizon, are unlikely to adapt to disturbances, thereby, leading to maladaptation and dissipation of gains from outsourcing (Susarla 2012). The danger then is that the services delivered through the outsourcing initiative could be out of step with changing business objectives of the client organization (Susarla 2012).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Particularly, papers on service contracts appear to focus more on projectbased services-e.g. IT software development (Banerjee and Duflo 2000, Gopal et al 2003, Kalnins and Mayer 2004, Susarla et al 2010, Susarla 2012, and offshore drilling (Corts and Singh 2004). The one-off relationship framed around a project that characterizes projectbased services differs significantly from the dynamics of repeated interactions found in the maintenance industry.…”
Section: Literature Reviewmentioning
confidence: 99%